(untitled) (IJM: Journal of Multidisiplinary, 2024)
This research seeks to unravel the thoughts on secularization from the perspective of Nurcholis Majid. The ideas of Nurcholis Majid's renewal, particularly this concept of secularization, have sparked controversy due to its association with Western (Christian) origins. Generally, secularization is seen as an effort to strip away worldly aspects or possessions from the church. On the other hand, secularism is a movement that advocates for worldly life without religious interference. The research method employed in this article is library research, conducted by examining and utilizing literature materials. In addition to being influenced by several figures (H. Abdul Madjid, Ibn Taymyah, Fazlur Rahman), Nurcholis Majid's ideas are also shaped by the socio-political-economic conditions of that time. When discussing secularization, Nurcholis Majid does not intend to impose secularism and turn Muslims into secularists. Instead, the goal is to free Muslims from the tendency to idolize inherently worldly values and to "worldlyize" those values. The purpose of Nurcholis Majid's secularization is to strengthen the worldly responsibilities of humans as Allah's stewards. Nurcholis Majid's concept of secularization is designed as a response to political issues in Indonesia in the 1970s.